Distinguishing research from clinical care in cancer genetics: theoretical justifications and practical strategies. - Hallowell, N; Cooke, S; Crawford, G; Lucassen, A; Parker, M (2009)
The relationship between clinical research and clinical care is often perceived as unclear, particularly in highly technological subspecialties. This ambiguity is illustrated in cancer genetics where research protocols are frequently used to provide access to procedures that may be offered as a clinical service in other specialties. The project on which this paper is based investigated lay and expert perceptions of the activities which take place within the cancer genetics clinic. Semi-structured interviews were conducted with 40 individuals who are involved in cancer genetics research in the UK, the majority (18 clinical geneticists, 10 genetic counsellors/nurse specialists) of whom also provide a clinical service. Interviewees emphasised the need to differentiate research from clinical care for service users, and provided regulatory, ethical, economic and translational justifications for distinguishing these activities. A number of strategies for differentiating research from clinical care were described by those who work as healthcare professionals, which involved deliberately displacing these activities in time and space. It is argued that by distinguishing research from clinical care clinical researchers are engaging in a form of boundary work which enables them to manage what they experience as a conflict of interest generated by the different roles they occupy within the cancer genetics clinic. Finally, we discuss the implications of these findings for the process of informed consent.